EGF-coated gold nanoparticles provide an efficient nano-scale delivery system for the molecular radiotherapy of EGFR-positive cancer. - Song, L; Falzone, N; Vallis, K (Taylor and Francis, 2016)
Purpose Radiolabeled antibodies and peptides hold promise for molecular radiotherapy but are often limited by a low payload resulting in inadequate delivery of radioactivity to tumour tissue and, therefore, modest therapeutic effect. We developed a facile synthetic method of radiolabeling indium-111 ((111)In) to epidermal growth factor (EGF)-gold nanoparticles ((111)In-EGF-Au NP) with a high payload. Materials and methods EGF-Au NP were prepared via an interaction between gold and the disulphide bonds of EGF and radiolabeled using (111)InCl3. Targeting efficiency was investigated by quantitating internalized radioactivity and by confocal imaging following exposure of MDA-MB-468 (1.3 × 10(6) EGFR/cell) and MCF-7 (10(4) EGFR/cell) cells to Cy3-EGF-Au NP. Cytotoxicity was evaluated in clonogenic assays. Results The proportion of total administered radioactivity that was internalized by MDA-MB-468 and MCF-7 cells was 15% and 1.3%, respectively (mixing ratio of EGF:Au of 160). This differential uptake in the two cell lines was confirmed using confocal microscopy. (111)In-EGF-Au NP were significantly more radiotoxic to MDA-MB-468 than MCF-7 cells with a surviving fraction of 17.1 ± 4.4% versus 89.8 ± 1.4% (p < 0.001) after exposure for 4 h. Conclusions An (111)In-labeled EGF-Au nanosystem was developed. It enabled targeted delivery of a high (111)In payload specifically to EGFR-positive cancer cells leading to radiotoxicity that can be exploited for molecularly targeted radiotherapy.